2017
DOI: 10.1515/hf-2017-0059
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility of hydroxyl groups in anhydride modified wood as measured by deuterium exchange and saponification

Abstract: Acetylated wood (WAc) shows improved properties largely due to the reduced amount of water in its cell wall, but the exact mechanism of water reduction remains unclear. Acetylation reduces hydroxyl (OH) content by acetyl (Ac) substitution but may also limit water access to unmodified OH groups by steric hindrance. In the present work, the accessibility of OH groups in acetylated or propionylated Radiata pine (Pinus radiataD. Don) wood (WAcand WPr) was investigated by deuterium exchange, saponification in sodiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 11 publications
4
42
0
Order By: Relevance
“…Different types of medium of transport for the percolating network have been proposed [103][104][105]. Inhibition of percolation in modified wood may occur through the filling of nanopores and physical blocking of the solute molecules [62][63][64][65][66][67][68][69][70]. Solute exclusion was identified as an appropriate technique to test this theory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different types of medium of transport for the percolating network have been proposed [103][104][105]. Inhibition of percolation in modified wood may occur through the filling of nanopores and physical blocking of the solute molecules [62][63][64][65][66][67][68][69][70]. Solute exclusion was identified as an appropriate technique to test this theory.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted to investigate whether steric hindrance of water molecules by acetyl groups plays a role in MC reduction in acetylated wood [60,[62][63][64][65]. In a recent study, Beck et al [66] showed that acetylation reduced OH accessibility to a greater extent than would be predicted if OH substitution was solely responsible for accessibility reduction. This suggests that steric hindrance further reduces the accessibility of water molecules to unmodified OH groups in acetylated wood.…”
Section: Wood-water Relationships In Modified Woodmentioning
confidence: 99%
See 1 more Smart Citation
“…In acetylation, wood reacts with acetic anhydride, producing acetic acid as a by-product [90]. During the reaction, accessible hydroxyl groups are replaced with acetyl groups, thus reducing the number of hydroxyl groups accessible for water molecules [91,92]. In addition, acetylation swells the cell wall, leaving less available space for water.…”
Section: Acetylationmentioning
confidence: 99%
“…So far, DVS with deuterium exchange has been applied to determine the accessible OH group content mostly in wood (Beck et al 2018;Kymäläinen et al 2015Kymäläinen et al , 2018Popescu et al 2014;Rautkari et al 2013;Thybring et al 2017), although some accessibility studies have been done to other cellulosic materials as well, e.g. bacterial cellulose (Lee et al 2011).…”
Section: Introductionmentioning
confidence: 99%